Knowledge about first aid of childhood emergency conditions among caregivers attending primary care centers in Bahrain – A cross-sectional study - Hasan Ali Al Haddad; Mahmood Alawainati; Hawra Fawzi Hasan; Hasan Abduljabbar Husain; Sadiq Mubarak; Ali Husain Sanad (Journal of Family Medicine and Primary Care, 2025)
Background: Child injuries pose a significant global public health concern and are considered a leading cause of child mortality. This study aimed to determine the knowledge of first aid measures for common childhood emergencies among caregivers in Bahrain. Materials and Methods: A cross-sectional study was conducted in eight primary healthcare centers across Bahrain, using a multi-stage sampling method. Caregivers aged 18 and older were invited to participate in the study and fill out a self-administered questionnaire that assessed sociodemographic characteristics, prior first aid training, and knowledge regarding first aid for childhood emergency conditions. Descriptive and inferential analyses were performed. Results: A total of 490 caregivers were included. Most participants were females (n = 357, 72.9%), aged between 25 and 35 years old (n = 202, 41.2%), and had a university or postgraduate certificate (66.9%). Nearly two-thirds (n = 308, 62.9%) of the caregivers did not complete any first aid courses. The average score of correct answers was 7.3 ± 2.4 out of 14. Most caregivers correctly identified first aid measures for electric shocks (84.5%) and fall-related injuries (78%). In contrast, low levels of knowledge were seen among caregivers regarding the management of febrile convulsions (11.8%), ankle sprains (29.0%), and epistaxis (36.5%). Additionally, caregivers who had higher academic levels (P < 0.001) and income (P < 0.001), caregivers who were retired (P = 0.003), older caregivers (P < 0.020), and those who had undertaken practical first aid courses (P < 0.001) exhibited higher knowledge about first aid measures compared to their counterparts. Conclusion: This study revealed relatively low levels of knowledge regarding first aid for childhood emergency conditions among caregivers in Bahrain. Practical first aid courses are encouraged to improve knowledge of childhood emergencies. Furthermore, enhanced educational programs focusing on areas of low knowledge could significantly improve outcomes for children in emergencies.